Legal issues on China’s maritime energy corridor security from the perspective of the Russia-Ukraine conflict - Li, Meng; Leng, Ling; Li, Jiayu; Ma, Chenkun; Zhang, Heyang (Frontiers in Marine Science, 2025)
The sanctions and embargoes resulting from the Russia-Ukraine conflict have triggered non-traditional risks, presenting significant challenges to international cooperation. Given the escalating situation concerning China’s sustainable maritime energy transport corridors, the establishment of a security governance mechanism for these corridors is urgently needed. However, upon examining and analyzing the legal foundation of China’s sustainable maritime energy transport corridors, it becomes evident that several issues persist. These include the limited effectiveness of conventions related to maritime energy transport corridors, the absence of cohesive security governance efforts among different entities, and inadequate coordination mechanisms. These challenges hinder traditional security governance mechanisms from effectively addressing the security issues surrounding energy corridors in the backdrop of the Russia-Ukraine conflict. To address this, China should institute a security governance mechanism for maritime energy transport corridors by promoting the objectives of fostering an energy community with a shared future, adhering to a comprehensive approach to national security, and upholding the principle of risk prevention. Specifically, this entails the need to develop specialized conventions for maritime energy transport, enhance multilateral security cooperation agreements among states along these routes, and establish an international legal framework to safeguard maritime energy corridors. Furthermore, a diverse cooperation network should be established among coastal states hosting energy corridors and international organizations under the guidance of the United Nations. Additionally, a cooperation mechanism and a varied dispute prevention and resolution system should be instituted to pave the way for the legal protection of sustainable maritime energy corridor security.